DIGITALIZATION OF POSTGRADUATE EDUCATION AS AN IMPORTANT COMPONENT OF THE DIGITAL TRANSFORMATION OF SOCIETY - Deineha, Iryna (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2023)
Currently, humanity has faced the fact: knowledge is updated faster than the change of generations is happens. This necessitates significant changes in education itself. In today's conditions, digitalization of postgraduate education is an important component of the digital transformation of society. The purpose of scientific research is to generalize and analyze the directions of digitization of post-graduate education institutions as an important component of the digital transformation of society. The study emphasized that: the digitalization of education should precede the digitalization of all other areas of social activity, since it is here that the social, psychological, general cultural and professional foundations for the digital transformation of society are formed. The research was conducted using the bibliographic method, the method of structural-scientific analysis, comparison and systematization. This made it possible to determine the expediency of maximum use of modern digital technologies in the educational process of adults. Result. It was determined that postgraduate education should be considered not only as a system of professional development and retraining of qualified specialists, but also as lifelong learning. Postgraduate education institutions should use digital technologies everywhere: to manage and organize the institution's activities, to ensure the educational process, to carry out online education; also, it is necessary to encourage both teaching staff and students to develop their own digital competence – which is a guarantee of a highly qualified and competitive specialist. Conclusions. Digital technologies make life easier, optimizing routine processes, leveling borders in the educational space that goes beyond the borders of one's country and continent. On the other hand, digitalization processes increase requirements for the level of professional training of employees, increasing competition in the labor market. There is an urgent need for a highly qualified specialist who, after undergoing retraining or advanced training, will possess certain competencies and will be able to effectively solve tasks independently and (or) as part of a team, showing activity, responsibility, perseverance and creativity. Therefore, the problems of digitalization of postgraduate education should be considered on a par with the digitalization of higher and secondary education and are an important component of the digital transformation of society as a whole